1994
DOI: 10.1093/oxfordjournals.humrep.a138747
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of human chorionic gonadotrophin in the outcome of early pregnancy after in-vitro fertilization and spontaneous conception

Abstract: This prospective study analyses the value of the beta-subunit of human chorionic gonadotrophin (beta-HCG) in 120 pregnancies obtained after in-vitro fertilization (IVF)--embryo transfer. Spontaneous conception cycles (n = 16) were also analysed allowing a comparison between these two forms of conception. Of the 120 clinical pregnancies, 48 started as single gestations and 50 started with two or more sacs. There were 14 clinical abortions and eight ectopic pregnancies. All subjects had blood samples taken under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 12 publications
1
36
0
Order By: Relevance
“…A number of studies have reported that β-hCG level represents trophoblastic mass and function and is predictive of pregnancy outcomes [1,[3][4][5][6][7], yet early β-hCG values after frozen embryo transfers have not studied. We further evaluated whether vitrification of day 3 embryos have an effect on β-hCG level of early pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have reported that β-hCG level represents trophoblastic mass and function and is predictive of pregnancy outcomes [1,[3][4][5][6][7], yet early β-hCG values after frozen embryo transfers have not studied. We further evaluated whether vitrification of day 3 embryos have an effect on β-hCG level of early pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The embryos were washed and cultured in cleavage medium (G-1, Vitrolife Sweden AB, Sweden) with 12 % SSS and incubated at 6 % CO 2 , 37 o C incubators for 48 h before being frozen. Embryonic development was assessed on Day 3 after oocyte retrieval with an inverted microscope using routine examination of: [1] the number of blastomeres; [2] the degree of cytoplasmic fragments; [3] the uniformity of blastomeres. Embryos morphology was scored as: grade 1, equal blastomeres with no obvious fragmentation; grade 2, <20 % fragmentation and/or unequal blastomeres; grade 3: 20-50 % cytoplasm fragmentation; grade 4: >50 % cytoplasm fragmentation.…”
Section: Fertilization and Embryo Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Our means to monitor normal pregnancy development are mainly by ␤hCG measurements at the early stages of pregnancy and ultrasound parameters at later stages. Pregnancies with low initial ␤hCG values were previously shown to have a poor prognosis in a multitude of studies (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Ultrasonographic parameters have also been stressed as predictors of early pregnancy outcome (19 -27).…”
Section: Discussionmentioning
confidence: 99%
“…Human chorionic gonadotropin level dynamically increases during early gestatation. Low levels of serum hCG in early pregnancy have been reported as a predictor of poor pregnancy outcome such as chemical and ectopic pregnancies as well as spontaneous miscarriage (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). However, the contribution of patients' characteristics and IVF treatment variables to low serum hCG level in early pregnancy has not been investigated.…”
mentioning
confidence: 99%